Kv7 channel inhibition increases hypoxic pulmonary vasoconstriction in endotoxemic mouse lungs - Turzo, Maurizio; Spöhr, Fabian; Lasitschka, Felix; Weigand, Markus A.; Busch, Cornelius (Experimental lung research, 2020)
Hypoxic pulmonary vasoconstriction (HPV) regulates regional pulmonary blood flow in order to match regional ventilation to preserve arterial oxygenation. HPV is impaired in patients with sepsis or acute respiratory distress syndrome (ARDS). Endotoxemic mice show reduced HPV and recent evidence suggests a central role of voltage gated potassium channel 7 (Kv7) in regulating HPV. Therefore, we tested the hypothesis if Kv7 is induced and inhibition of Kv7 increases HPV in endotoxemia. Isolated lungs of LPS-pretreated and untreated animals were perfused with and without specific inhibitors of Kv7 (linopirdine (LI) 0, 0.1, 1 and 10 µM) or Kv7.1 (HMR1556 100 nM). Pulmonary artery pressure (PAP) during normoxic (FiO2 0.21) as well as hypoxic (FiO2 0.01) ventilation were obtained. Expressions of Kv7 composing (KCNQ1-5) as well as auxiliary subunits (KCNE1-5) were measured in mouse lungs with and without endotoxemia. HPV was impaired in lungs from LPS mice (16 ± 7% vs 105 ± 13% control, p < 0.05). Perfusion of control lungs with 10 µM LI or 100 nM HMR1556 did not affect HPV (LI 105 ± 12% vs 105 ± 13% vehicle, HMR1556 100 ± 6% vs 98 ± 26%, P = NS). In LPS mice perfusion with 10 µM LI (74.2 ± 7% vs. 16 ± 7% vehicle, P < 0.05) or HMR1556 100 nM augmented HPV (74 ± 28% vs. 15 ± 17% vehicle, P < 0.05). KCNQ1, 4 and 5 gene- and protein expressions as well as KCNE1, 2 and 4 gene expressions were unaltered in endotoxemic lungs. KCNE3 gene and protein expressions were increased in lungs of LPS treated mice (3.1 ± 1.3-fold and 1.8 ± 0.3-fold, respectively, P < 0.05 for both). Endotoxemia does not alter KCNQ1, 4 and 5 gene and protein expressions but increases pulmonary KCNE3 gene and protein expression. In isolated perfused endotoxemic mouse lungs, perfusion with 10 µM LI or 100 nM HMR1556 augments HPV.
Gesehen am 23.09.2025